1996
DOI: 10.1098/rspb.1996.0230
|View full text |Cite
|
Sign up to set email alerts
|

Using higher-taxon richness as a surrogate for species richness: II. Local applications

Abstract: Recent analyses confirm that urgent attempts to catalogue the distribution of biological diversity may be facilitated by focusing at the level of genera or families rather than species. However, questions remain over the application of higher-taxon surveys to identify networks of priority areas for conservation action. Is the close spatial match between species and higher-taxon richness at global and regional scales re iterated when sites are locally distributed? How much money is saved by the higher-taxon app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(16 citation statements)
references
References 23 publications
1
15
0
Order By: Relevance
“…In several studies, generic diversity of ants has been shown to be correlated with species richness and so can be used as a good predictor of species richness for large (79) and local scales (80)(81)(82)(83)(84)(85), with some interesting exceptions (86). Other advantages and disadvantages of using higher taxonomic rank have been summarized by Balmford et al (87) and Gaston (88), but all such summaries highlight the value of higher taxonomic level analyses. Exotic genera.…”
Section: Methodsmentioning
confidence: 99%
“…In several studies, generic diversity of ants has been shown to be correlated with species richness and so can be used as a good predictor of species richness for large (79) and local scales (80)(81)(82)(83)(84)(85), with some interesting exceptions (86). Other advantages and disadvantages of using higher taxonomic rank have been summarized by Balmford et al (87) and Gaston (88), but all such summaries highlight the value of higher taxonomic level analyses. Exotic genera.…”
Section: Methodsmentioning
confidence: 99%
“…In fact, over the last 20 years, conservation biologists have discussed the use of surrogate species in conservation planning at great length, debating both the advantages and disadvantages of this approach (Murphy et al 2011). There are several different types of surrogacy (Magurran 2004), such as: (i) cross-taxon, where high species richness in one taxon is used to infer high species richness in others (Mortiz et al 2001); (ii) within-taxon, where generic or familial richness is treated as a surrogate of species richness (Balmford et al 1996); and (iii) environmental, where parameters such as temperature or topographical diversity are assumed to reflect species richness (Magurran 2004). Another approach is based on "community concordance" and describes the degree to which patterns in community structure in a set of sites are similar in two different taxonomic groups (Paszkowski & Tonn 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Although the cost of running such programs may vary by several orders of magnitude among taxa and countries [40], surrogates may provide a shortcut to useful biodiversity data (e.g., [41,42]). Further, appropriately designed sampling schemes may lessen the required coverage if implemented accurately [35].…”
mentioning
confidence: 99%